Posterior Arthroscopic Treatment of a Massive Effusion in the Flexor Hallucis Longus Tendon Sheath Associated with Stenosing Tenosynovitis and Os Trigonum - Ichiro Tonogai; Koichi Sairyo (Case Reports in Orthopedics)
We report a rare case of massive accumulation of fluid in the flexor hallucis longus tendon sheath with stenosing tenosynovitis and os trigonum. A 34-year-old woman presented to our hospital with pain and swelling in the posteromedial aspect of the left ankle joint after an ankle sprain approximately 8 months earlier. There was tenderness at the posteromedial aspect of the ankle, and the pain worsened on dorsiflexion of the left great toe. Magnetic resonance imaging revealed massive accumulation of fluid around the flexor hallucis longus tendon. We removed the os trigonum, performed tenosynovectomy around the flexor hallucis longus, and released the flexor hallucis longus tendon via posterior arthroscopy using standard posterolateral and posteromedial portals. At 1 week postoperatively, the patient was asymptomatic and able to resume her daily activities. There has been no recurrence of the massive accumulation of fluid around the flexor hallucis longus tendon as of 1 year after the surgery. To our knowledge, this is a rare case report of extreme massive effusion in the flexor hallucis longus tendon sheath with stenosing tenosynovitis and os trigonum treated successfully by removal of the os trigonum, tenosynovectomy around the flexor hallucis longus, and release of the flexor hallucis longus tendon via posterior ankle arthroscopy.